2022
DOI: 10.3390/nano12030340
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Thermal Synthesis of g-C3N4/ZnO Composites for the Degradation of 5-Fluoruracil Cytostatic Drug under UV-LED Irradiation

Abstract: Graphitic carbon nitride (g-C3N4) was used to enhance the photocatalytic activity of ZnO nanoparticles for the degradation of 5-fluorouracil (5-FU) cytostatic drug under UV-LED irradiation. CN/ZnO composites were synthetized by an easy one-pot thermal method, varying the g-C3N4 loading, i.e., from 10 to 67 wt% and a post-thermal exfoliation in air. The physicochemical and optical properties of the materials were analyzed by several techniques. CN/ZnO composites showed a coral-like structure of spherical ZnO wu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 64 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…Figure a shows the Kubelka-Munk function of the UV–vis DRS of the prepared ZnO, g-C 3 N 4 , and the ZnO/g-C 3 N 4 composite after the degradation reaction of BPE. It was observed that the prepared ZnO and g-C 3 N 4 had the absorption edge at about 390 and 430 nm, respectively. Moreover, the absorption edge of the prepared ZnO/g-C 3 N 4 composite was significantly red-shifted to a higher wavelength compared to both pure ZnO and g-C 3 N 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a shows the Kubelka-Munk function of the UV–vis DRS of the prepared ZnO, g-C 3 N 4 , and the ZnO/g-C 3 N 4 composite after the degradation reaction of BPE. It was observed that the prepared ZnO and g-C 3 N 4 had the absorption edge at about 390 and 430 nm, respectively. Moreover, the absorption edge of the prepared ZnO/g-C 3 N 4 composite was significantly red-shifted to a higher wavelength compared to both pure ZnO and g-C 3 N 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, g-C 3 N 4 has received great attention as an interesting photocatalyst for wastewater detoxification, hydrogen production, and photoreduction of CO 2 under visible light irradiation. Pure g-C 3 N 4 possesses a moderate band gap of ∼2.7 eV, which enables it to be excited by visible light up to 460 nm. Furthermore, metal-free g-C 3 N 4 has several features required for photocatalysis reactions, such as a π-conjugated electronic structure, layered crystal structure, low cost, nontoxic nature, high chemical and thermal stability, high electron conductivity, and facile fabrication. , However, the photocatalytic efficiency of g-C 3 N 4 is greatly reduced because of the low quantum efficiency and fast recombination rate of the photogenerated electron–hole pairs. , Hence, to reduce the drawbacks of g-C 3 N 4 , several methods such as coupling with metal organic frameworks, covalent organic frameworks and other semiconductors (metal oxides and metal sulfides), doping with elements, and monitoring its structure and morphology have been proposed. , For instance, Kuila et al reported the synthesis of cerium ion-adsorbed g-C 3 N 4 for enhancing the photocatalytic degradation of methylene blue dye under sunlight irradiation . de Sousa et al prepared a ternary photocatalyst of ZnO/g-C 3 N 4 /carbon xerogel, which was used in efficient photocatalytic degradation of 4-chlorophenol under visible light irradiation .…”
Section: Introductionmentioning
confidence: 99%
“…Both TEM elemental mapping ( Figure 2 e) and EDX analysis (Figure S2) of CoVO/PCN showed Co, V, O, and C, N elements visually belonging to CoVO and PCN. The coexistence of CoVO lattices and amorphous PCN observed in Figure 2 c,d illustrate that a tight heterojunction between CoVO and PCN was formed in the hybrid [ 38 ]. Additionally, the BET-specific surface areas of PCN and 3 wt % CoVO/PCN were 62 and 56 m 2 g −1 (Figure S1b) , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Co 2p spectrum in Figure 3 b is described as two peaks of Co 2P 2/1 at 797.3 eV and Co 2P 2/3 at 781.1 eV, with additional satellite peaks situated at 787.1 eV and 803.5 eV [ 36 ]. The V 2p spectrum in Figure 3 c is located at 524.6 eV and 517.2 eV corresponding to the V 2p 1/2 and V 2p 3/2 [ 36 , 38 ]. The O 1s spectrum is shown in Figure 3 d and can be split into three peaks at binding energies of 530.3 and 532.0 eV, which were attributed to the Co–O bond and the oxygen in the surface hydroxyl groups (C–OH) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the utilization of methane formed during the extraction of natural resources, the process of the deactivation of catalysts occurring under the conditions of a deep oxidation reaction based on La-Ca-Mn-Co perovskites was considered in [ 8 ] by the in situ XRD method. In [ 9 ], a g-C 3 N 4 /ZnO nanocomposite was used for the degradation of 5-fluoruracil cytostatic drug under UV–LED irradiation.…”
mentioning
confidence: 99%